Parallel texts from the Swedish National Food Agency - Dahlberg, Simon; Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Parallel texts downloaded from the agency's website.

Parallel texts downloaded from the website of the Swedish National Food Agency.
The files that were downloaded were all pdf files. The txt files that are available are the result of running the pdf files through the pdftotext command from an ubuntu shell.

Parallella texter nedladdade från Livsmedelsverkets webbplats. Det som nedladdades var pdf-filer. De txt-filer som finns tillgängliga är resultat ur en körning av kommandot pdftotext i ubuntu-skal.
Parallella texter från Livsmedelsverket
Keywords: Child Nutritional Physiological Phenomena; Barns näringsfysiologi; Legislation, Food; Livsmedelslagstiftning; Nutritional Requirements; Näringsbehov; General health and well-being; Allmän hälsa och välbefinnande; Agriculture and rural industry; Jordbruk och landsbygdsnäring; Nutrition and Dietetics; Näringslära och dietkunskap; Languages and Literature; Språk och litteratur; Public health; Folkhälsa; Public Health, Global Health and Social Medicine; Folkhälsovetenskap, global hälsa och socialmedicin